Strategies in performing a multi-level C-test: applying Think-Aloud Protocols - Babaii, Esmat (Вестник Томского государственного университета. Филология)
The aims of this study were: 1) to identify the cognitive strategies that Russian EFL learners apply while taking a multi-level C-test; 2) to examine the correlation between the level of complexity of a C-test and the frequency of the usage of the cognitive strategies. The Think-Aloud Protocols method allowed to reveal seven cognitive strategies (predicting, summarizing, questioning, making connections, re-reading/using fix-ups, identifying a problem, and reflecting). The results of chi-square tests indicate that texts with different complexity levels can trigger different type of processing used by the test-takers.